“La imagen institucional del GAD municipal de baños de agua santa y su incidencia en los usuarios externos en el período julio – diciembre 2015” - Romero Miranda, Doris Adriana (2017)
Institutional Image of the Autonomous Municipal Government of the Canton Baños de Agua Santa and its impact on external users was developed in the period July, December 2015. ABSTRACT: The development of this research work establishes its bases in concepts, theories, tendencies and guidelines on Institutional Image of the Autonomous Municipal Government of the Canton Baños de Agua Santa, located in the province of Tungurahua; And its impact on external users. This research is divided into five chapters. Chapter one, describes research references that are developed in the problem approach, description of objectives; Which are related to the justification, relevance, and importance of the study that establishes its bases in the identified problem. The theoretical foundation, includes, theories, as scientific, theoretical, conceptual and doctrinal support of the proposed problem; This research work, Institutional Image of the Autonomous Municipal Government of the Canton Baños de Agua Santa and its impact on external users was developed in the period July, December 2015. This study researched about the Corporate Image, its main characteristics, components, factors and importance as a factor for the development of the entities; In addition explained about the Public Opinion; communication, and their theories. Third chapter, on the other hand, works on the the methodological process that was applied to carry out the research, revealing how the information gathered for the research execution was obtained and how it was treated, This allowed to verify the hypothesis of our subject, to construct new knowledge about the researched topic. Fourth Chapter presents conclusions and recommendations, after having fulfilled the investigation process, on the basis of the conclusions were established the recommendations with the intention that they are applied to improve the identity of the GAD of Baños de Agua Santa Fifth and last chapter presents the proposal of communication strategies, which aims to be a guide to improve the image of GADMBAS